PEMBERDAYAAN PERAJIN INDUSTRI ROTAN PASCA BENCANA OLEH DINAS PERDAGANGAN DAN PERINDUSTRIAN KOTA PALU - Wilda Maulidia; Hasna Azmi Fadhilah; Hendrawati Hamid (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2020)
This research titled is “Empowerment of Rattan Industry Craftsmen After Disasters by Department of Trade and Industry in Palu City Central Sulawesi Province”. The purpose of this research is to find out and analyze the empowerment process, supporting factors and inhibiting factors faced, as well as efforts made by the Department of Trade and Industry to overcome obstacles in the empowerment of rattan industry crafters in the aftermath of a disaster. The research method used by the author in this study is descriptive qualitative.The data collection techniques are interviews, documens and observations. The data analysis techniques in this study are data reduction, data presentation and data verification. The result of this research apprenticeship show that empowerment of crafters in managing the rattan industry after disaster has been carried out. But in the implementation, the empowerment process has not been carried out optimally. Because the mindset of craftsmen who are still using old mindset, the absence of Standard Operating Procedures regarding the rattan industry which results in an ineffective upstream and downstream system, Limited funds owned by the government in providing assistance and the independence of the craftsmen in producing raw materials supporting the rattan industry. After disaster, Department of Trade and Industry has made efforts to overcome obstacles with : make a Standard Operating Procedures dan rebuilding the upstream and downstream systems. In addition, Department of Trade and Industry has also allocated funds in accordance with needs and provides socialization in changing the mindset of rattan industry crafters and training to develop rattan industry businesses. The authors suggests to the city government that in the future in making a development and empowerment planning, the city government must fist make Standard Operating Procedures. As well as the process of the rehabilitation and reconstruction stages, the government must better understand its tasks and functions Keyword : Empowerment, Craftsmen, Rattan Industry, Disaster